Cataract surgery and the risk of progression of macular degeneration. Issue 1 (21st January 2023) - Bhandari, Sanjeeb; Chew, Emily Y.
Abstract : Purpose of review: Cataract surgery improves vision loss due to cataracts in eyes with co-existing age-related macular degeneration (AMD), but whether surgery itself pose an increased risk for the progression of AMD has been of concern to both physicians and their patients. This review describes evidence on cataract surgery and its impact on the progression of AMD. Recent findings: Recent evidence suggests that cataract surgery does not increase the risk for progression of AMD. Summary: Cataract surgery should be discussed in patients with both AMD and visually significant cataract. Patients should be reassured that the cataract surgery will not increase the risk of AMD progression. In patients with AMD, especially those with the more severe intermediate stage and those with advanced AMD in the fellow eye, the natural course of progression to late AMD is high. The importance of vigilant follow-up needs to be emphasized for the detection of natural progression of the disease and early initiation of treatment should signs of neovascularization develop.